Evaluasi Ketangguhan Alumunium terhadap Beban Dinamis melalui Pengujian Impak Charpy Takikan V - Trisanti, Trisanti; Susanto, Dian; Kasda, Kasda; Rachman, Maulana; Irawan, Yusril (FAKULTAS TEKNIK UNIVERSITAS SUBANG, 2023)
This study evaluates the toughness of aluminum against dynamic loads through V notch Charpy impact testing. Tests were conducted on aluminum specimens with varying temperatures to observe their effect on impact energy, fracture type, and transition temperature. The methodology involved the use of an impact machine to present consistent and reliable data. The main findings include the influence of V notches on the impact characteristics of aluminum, identifying critical zones that may experience deformation or cracks. Results show that impact energy and the predominance of ductile fracture increase with higher temperatures. At low temperatures, brittle fracture is dominant. A transition temperature curve was successfully drawn, showing the change in material properties from ductile to brittle. It has been demonstrated that V notch Charpy impact testing is useful for evaluating aluminum toughness and can help improve the design and safety of aluminum components in dynamic load applications.